Comparative analysis of the management profiles of selected secondary schools in the National Capital Region - Casing, Reynaldo Elardo 1968- (2008)
This study compared and analyzed the management profiles of selected secondary schools both public and private in the National Capital Region. It also studied the leadership styles of the principals. Using qualitative and quantitative or mixed design method, the study covered selected public and private secondary schools in the division of Caloocan, Makati, Manila, Quezon City, and Valenzuela involving principals and their respective department heads, teachers, and students. Among the 3 classical leadership styles, the democratic or participative is still the style being used mostly by administrators. Since this is the first study on comparative analysis among public and private schools, the result may prove useful to the Department of Education as it aims to achieve quality basic education.